The role of competitive environment and strategy in the supply chain's agility, adaptability and alignment capabilities - Pedro Garrido-Vega; Macarena Sacristán-Díaz; José Moyano-Fuentes; Rafaela Alfalla-Luque (European Journal of Management and Business Economics, 2023)
Purpose – This paper analyses the way that the industry's competitive environment and the company's strategy influence the implementation of the supply chain's (SC’s) triple-A capabilities (agility, adaptability and alignment). Two competitive environment variables are analysed: competitive intensity of the industry and complexity of the SC. Two opposing competitive strategies are also considered: cost and differentiation. Design/methodology/approach – The hypotheses have been tested using data gathered via a questionnaire given to 277 Spanish manufacturing companies, and structural equation modelling has been used for the analysis. Findings – The results show that competitive intensity is the most influential factor followed by business strategy. SC complexity does not seem to affect agility. Moreover, although the competitive environment variables affect the business strategy, the latter has no mediating effects between the competitive environment and SC agility, adaptability and alignment capabilities. Originality/value – This study presents new insights into the environmental and strategic drivers linked to the implementation of SC agility, adaptability and alignment capabilities and offers guidelines to managers involved in SC management. 研究目的 – 本文分析產業的競爭環境和公司的策略如何影響供應鏈三A能力 (靈活性、適應能力和調整能力) 的實現。兩個競爭環境變數被分析, 就是產業的競爭強度和供應鏈的複雜性。同時, 兩個對立的競爭策略也被探討,就是價格和差異化。 研究方法 – 各個假設均以數據測試; 數據取自277間西班牙製造商囘應之問卷, 分析則以結構方程模型進行。 研究結果 – 研究結果顯示、競爭強度是最重要的影響因素, 其次是經營策略。供應鏈的複雜性似乎對靈活性沒有影響; 而且, 雖然競爭環境變數影響著經營策略, 但經營策略在競爭環境與供應鏈靈活性、適應能力和調整能力之間沒有起仲介效果。 研究的原創性 – 本研究就環境和策略如何驅動供應鏈靈活性、適應能力和調整能力方面提供了新的啓示, 亦為負責供應鏈管理的主管提供了指引。